Characterization of IMC layer and its effect on thermomechanical fatigue life of Sn–3.8Ag–0.7Cu solder joints - Che, Faxing (2013)
Intermetallic compound (IMC) growth was investigated under isothermal aging condition at 125 °C for up to 500 h. The evolution in the IMC morphology and microstructure were observed at four aging time conditions for 0, 120, 260 and 500 h, respectively. Solid state IMC growth thickness measurements were determined from scanning electron microscope (SEM) observations for Cu–Sn and Cu–Ni–Sn IMC systems. The Young’s modulus and hardness of the IMCs were determined by nanoindentation tests. A finite element analysis (FEA) was carried out to model the effect of the IMC layer on the solder joint thermal fatigue life. The nanoindentation mechanical properties of Cu6Sn5 and CuNiSn IMCs were modeled with different IMC thicknesses in the FEA simulation to study the effect of the IMC growth on the fatigue life of the solder joint. It was shown that the IMC layer reduces the fatigue life of the solder joints and thick IMC layer results in a lower fatigue life. In addition, thermal cycling test and analysis for plastic ball grid array (PBGA) package with Sn–3.8Ag–0.7Cu Pb-free solder joints was performed. The mean-time-to-failure (MTTF) for the PBGA solder joints was determined, which was used for validating the FEA simulation results.